The Effect of Aroma Therapy Olive Oil Massage to Pain Dysmenorrhea on Midwifery Level I and II Students at Tri Mandiri Sakti Institute of Health Sciences - Tria Nopi Herdiani; Mika Oktarina; Yeni Nuraeni (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Reproductive health problems are dysmenorrhea is a problem related with menstruation. research show the highest prevalence of menstrual pain in adolescent women, adolescent who experience dysmenorrhea report pain that interferes with daily activities. Handling to reduce pain during menstruation, one of which is using the olive oil aroma therapy aroma method. This research to determine the effect of aroma therapy olive oil massage pain dysmenorrhea on midwifery student level I and II Stikes Tri Mandiri Sakti Bengkulu.This study used a pre experiment in one group (one group pre-post test design) the dependent variable of pain before and after treatment. Sampling was done by accidental sampling technique using the criteria totaling 41 student who experience dysmenorrhea. The study was conducted from May to June 2017. Retrievel of data using the observatioan sheet and analyzed using compared mean paired T-test. The Result of the research: (1) At 41 people in the first and second grade obstetric students who had dysmenorrhea before the massive olive oil odor therapy aroma got the average pain scale 5,73 with the standard deviation 1,450. (2) In 41 subjects who had dysmenorrhea after the massage of olive oil odor therapy, the average pain scale was 5,00 with a standard deviation of 1,414. (3) There is massive effect of olive oil odor therapy to dysmenorrhea pain in female students of Level I and II Prodi DIII Midwifery Tri Mandiri Sakti Institute of Health Sciences Bengkulu. Keywords : aroma therapy, dysmenorrhea, massage